The Effect of Carbon Steel Pipeline Deterioration to Water Injection Quality and Pressure Drop in Tanjung Waterflood Injection Plant. - Migel Aldila; Iwan Febrianto; Akhmad Sudirman Saputra; Purnama Timur M.S; Ninik Purwatiningsih (Testing Center for Oil and Gas LEMIGAS, 2020)
In Tanjung, South Kalimantan, PT Pertamina EP (PEP) use secondary recovery (waterflood injection) for its technique for oil lifting. Low permeability reservoir condition make quality of water injection must be comply with low permeability reservoir requirement and the pressure injection must be around 1400 psig. In the common PEP injection plant, carbon steel pipeline is still used. Flakes accumulation and trapped oil could occur along with the deterioration of carbon steel pipeline. This matter can make the quality of requirements of injection water become worst. There were four data were analyzed; Oil content, TSS (Total Suspended Solid), Turbidity and Total Iron. The sample was taken at discharge pump and one of the injections well during 6 months. Â Averagely the result of value of total iron, turbidity and oil content in injection well are bigger than discharge pump while TSS has little fluctuation. In conclusion, deterioration carbon steel pipeline has effect to reduce quality water injection become worst and effect of roughness of pipeline due to carbon steel deterioration can make the pressure drop is higher in accordance with the length.